2022
DOI: 10.1002/cne.25312
|View full text |Cite
|
Sign up to set email alerts
|

Structural and molecular characterization of paraventricular thalamic glucokinase‐expressing neuronal circuits in the mouse

Abstract: The thalamic paraventricular nucleus (PVT) is a structure highly interconnected with several nuclei ranging from forebrain to hypothalamus and brainstem. Numerous rodent studies have examined afferent and efferent connections of the PVT and their contribution to behavior, revealing its important role in the integration of arousal cues.However, the majority of these studies used a region-oriented approach, without considering the neuronal subtype diversity of the nucleus. In the present study, we provide the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 74 publications
(116 reference statements)
2
9
0
Order By: Relevance
“…We also report here that the glucokinase (Gck) gene is most highly expressed in the PVT3 AL subtype, potentially linking recent reports of the unique attributes of glucokinase-expressing aPVT neurons (aPVT Gck ) to the PVT3 subtype [27,33]. NAcprojecting aPVT Gck neurons were shown to be activated by hyperglycemic conditions and negatively modulate sucrose-seeking behavior [27].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…We also report here that the glucokinase (Gck) gene is most highly expressed in the PVT3 AL subtype, potentially linking recent reports of the unique attributes of glucokinase-expressing aPVT neurons (aPVT Gck ) to the PVT3 subtype [27,33]. NAcprojecting aPVT Gck neurons were shown to be activated by hyperglycemic conditions and negatively modulate sucrose-seeking behavior [27].…”
Section: Discussionsupporting
confidence: 67%
“…Clusters were characterized by referencing top gene markers from each cluster with their spatial expression from Allen Brain Atlas ISH data and previous literature (Figure 1—figure supplement 2b, c, mouse.brain-map.org) [32]. From this comparison, we found that PVT neurons (4,067 nuclei; 62.0% of all neurons) expressed markers such as Gck , C1ql3 and Hcn1 , and were thus represented in neuron clusters 0, 2, 3 and 4 (Figure 1—figure supplement 2c, h) [3335]. Neurons associated with other brain regions surrounding the PVT and represented in our sample include: MD (cluster 1; 1,003 nuclei, 15.3% of neurons), IMD (cluster 5; 500 nuclei, 7.62% of neurons), principal nucleus of the posterior bed nucleus of the stria terminalis (BSTpr; cluster 6; 496 nuclei, 7.57% of neurons), and habenula (Hb; cluster 7; 489 nuclei, 7.46% of neurons) (Figure 1—figure supplement 2d-g, h, Supp.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Biomarkers with ≥ 2-fold differential expression, and per our Pubmed search not previously associated with other neurological conditions or processes include: FAM217B (family with sequence similarity 217 member B), QRICH2 (glutamine rich 2), KRT16 (keratin 16), ZNF333 (zinc finger protein 333). FAM217B has been reported to have repressed expression in ulcerative colitis and differentially expressed in glucokinase-positive neurons . QRICH2 regulates the formation of sperm flagella and when absent is associated with male infertility .…”
Section: Resultsmentioning
confidence: 99%
“…FAM217B has been reported to have repressed expression in ulcerative colitis 59 and differentially expressed in glucokinase-positive neurons. 60 QRICH2 regulates the formation of sperm flagella and when absent is associated with male infertility. 61 Variants in its homologue gene, QRICH1, are linked to a neurodevelopmental short stature syndrome.…”
Section: Differential Expressionmentioning
confidence: 99%